2015
DOI: 10.17951/ijsr.2014.3.0.5
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Factors of Public Employees’ Ganizational Commitment

Abstract: Purpose -The aim of this chapter is to shed some light on the antecedents of organizational commitment, the mediating role of job engagement and job satisfaction as determinants of organizational commitment within the public sector environment, and the effects that national cultural values may have on these relationships. Approach -This paper presents a review of the works that, from both theoretical and empirical points of view, explore the affecting factors of public employees' organizational commitment in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Various studies have concluded that monetary reward is the significant determinant that hit the motivational factor of the employee and affect their productivity in a positive manner [Uzonna, 2013;Weng et. al, 2015;Rakowska et. al, 2015].…”
Section: Monetary Rewardsmentioning
confidence: 98%
“…Various studies have concluded that monetary reward is the significant determinant that hit the motivational factor of the employee and affect their productivity in a positive manner [Uzonna, 2013;Weng et. al, 2015;Rakowska et. al, 2015].…”
Section: Monetary Rewardsmentioning
confidence: 98%
“…Accounting companies generally perceive long working hours, strict deadlines, and strict regulations. The fact is that accountants must comply with professional standards in order to ensure that their rights are appropriately protected (Rakowska, Valdes-Conca & Juana Espinosa, 2018). Therefore, rigid work practices and tight deadlines are prevalent in accountancy companies, known as a hierarchy in this study, and are unavoidable cultures.…”
Section: Sypniewska (2013)mentioning
confidence: 99%
“…The relationship between job satisfaction and organisational commitment is well established (Rakowska, Valdes-Conca & Juana-Espinosa, 2014). According to Sattar (2014), employee involvement and commitment are dependent on the level of job satisfaction.…”
Section: Relating Job Satisfaction and Organisational Commitmentmentioning
confidence: 99%